Vooya’s Digital Marketing Communication Strategy Improvement - Jason Winston Wibawa (iBuss Management, 2020)
Digital marketing communication strategy is the combination of internet and digital media platform as a promotion media for a company to use as their marketing strategy. It shows a great prospect in future to replace traditional marketing strategy. Along with the emergence of education consultancy industry, Indonesia's education consultancy business starting to rely on the growth of digital marketing strategy to increase its customer interaction and improve its sales. Thus, the purpose of this research is to examine the digital marketing communication strategy techniques that Vooya could apply as their marketing strategy. Analysis throughout the Vooya's current marketing mix strategy, Indonesia's education consultancy market condition, Interview with Vooya's journey past participants, and Vooya's direct competitor's data was gathered and used for this research. Furthermore, the result for this research shows that search engines marketing, social media marketing, and online public relation are recommended for Vooya to apply to improve its sales.Keywords: Digital Marketing Communication Strategy, Education Consultancy,Customer Interaction, Sales Improvement.